Auditing of SARS-COV-2 Contagion and Transmission Protocols as a Stakeholder Management Tool - Muncinelli, Gianfranco; Pinheiro de Lima, Edson; Vecchia, Augusto Carlos Dalla; Moro, Luis; Deschamps, Fernando; Gouvea da Costa, Sergio E.; Cestari, José Marcelo A. P. (Frontiers in Sustainability, 2021)
Governments and companies in all affected countries have taken measures to prevent, on the one hand, the rapid spread of the virus among the population and, on the other hand, to alleviate the economic and commercial consequences of the crisis that is already changing the daily functioning of the population. the companies. The COVID-19 pandemic has radically and unexpectedly transformed the global economic landscape. The objective of this work is to demonstrate a set of information that can meet the expectations of the internal and external stakeholders of an organization concerned with constructively relating to its stakeholders - aiming at the possibility of carrying out the work and serving customers in the context of pandemic. The research method is the study based on the literature review process with a focus on information and research systems, books and a manufacturer's case study. It also has practical data - information collected from audits carried out. Stakeholders' expectations and interests are connected to this issue and can be aligned through an Audit of Contagion and Transmission Protocols of SARS-COV-2.